Estudo do sentimento de culpa na teoria Freudiana (1892-1924) - Rainha, Amanda Tardivo (2013)
This study aimed to perform a trace of the concept sense of guilt in Freudian theory from the trajectory performed by Sigmund Freud in his complete works in the period between 1892 and 1924. From this, we demonstrate how this concept was built and changes along with the development of this theory. For this, we examined Freud?s writings in chronological order of publication and we seek to understand, beyond its manifestations, the origin of the sense of guilt and its development in his metapsychological aspects. So, in the end, we were able to explain this subject from its economic, dynamic and topographic aspects, allowing us, from our point of view, provide a deeper understanding and systematization of the theme